Accounting toward sweet success: Treadwell's Ice Cream. Issue 1 (3rd January 2017) - Lam, Miranda; Guo, Hongtao; McGee, Paul
Abstract : Synopsis: Tom Gould, an entrepreneur, had been operating Treadwell's Ice Cream, a small ice cream restaurant since 2000. Treadwell's Ice Cream had been preparing its financial statements under cash basis. Tom Gould turned over all his receipts, both personal and business expenses, to his bookkeeper who entered them into QuickBooks. At tax time, his tax accountant excluded non-qualifying expenses from the tax filing. Periodically, Tom met with his bookkeeper to determine the results of operations and financial position at the end of that period of time. Most of Treadwell's transactions were easily recognized by Tom, who preferred to pay all expenses by cash rather than credit. However, the bookkeeper had not been separating operating from non-operating activities, and had been using multiple accounts to record the same or similar costs. Therefore, the current income statement and balance sheet were not appropriately categorized and organized. In addition, since the bookkeeper was not a tax account, business expenses had been mixed with Tom Gould's personal expenses on the income statement. There were no adjustment to the income statement after the tax accountant identified non-qualifying expenses when preparing tax filing. As Tom and his wife were considering turning over more day to day operations to his son and hiring a non-family member as a manager to help his son, he would need the books to provide an accurate picture of the business. Research methodology: Primary source materials included interviews with the owner, Thomas Gould, his son, Michael Gould, and their Accountant, Tom Mallas. Secondary source materials included monthly and annual financial data from QuickBooks (monthly data are available upon request but are not relevant to the case discussion). Other secondary source materials included geographic, economic, industry, and competitors' information. Relevant courses and levels: This case is well suited for an introductory level undergraduate financial accounting course, after accrual accounting and accounting information systems (accounting cycles) have been introduced. When analyzing this case, students will apply concepts and principles of financial statement preparation. The case is also appropriate to serve as a review of accrual accounting, and of income statement and balance sheet preparation at the beginning of an intermediate level financial accounting course. Students can be asked to reformat the income statement from the single-step format to the multiple-step format. By working through financial statements with common errors found in small businesses, students can practice identifying these errors, thus providing a review of the various sections of the income statement and prepare students for more in-depth discussions of each section. In a tax course, this case can stimulate discussions on non-qualifying expenses and common shortcomings in small business accounting.